Sponsor backing in Asian REIT IPOs - Wong, Woei Chyuan; Ong, Seow-Eng; Ooi, Joseph T. L. (Springer US, 2013)
This paper tests the significance of sponsors in REIT IPOs viz-a-viz quality certification, signal of firm value, and commitment to alleviate moral hazard concerns. We model the REIT pricing and sponsor share retention decisions within a simultaneous decision framework as motivated by Grinblatt and Hwang (Journal of Finance 44:393–420, 1989).We find positive and significant bidirectional relationship between the fraction of shares held by the sponsor in IPO and underpricing which is consistent with Grinblatt and Hwang’s (Journal of Finance 44:393–420, 1989) signaling model. Our results also support the commitment hypothesis that developers that spin off REITs tend to hold more shares at IPO, possibly to compensate investors for the potential moral hazard problems in the aftermarket.